A Theory of Collateral Requirements for Central Counterparties - Wang, Jessie Jiaxu; Capponi, Agostino; Zhang, Hongzhong (Management Science, 2022)
This paper develops a framework for designing collateral requirements in a centrally cleared market. Clearing members post collateral—initial margins and default funds—to increase their pledgeable income, thereby committing to risk management. The two types of collateral, however, are not perfect substitutes. By achieving loss mutualization, default funds are economically more efficient than initial margins in aligning members’ incentives for risk management ex ante. The optimal mix of collateral resources balances the efficiency in providing incentives with their relative opportunity costs. Our model predicts increased use of initial margins under stringent capital requirements and of default funds under distressed market scenarios. This paper was accepted by David Simchi-Levi, finance.